Analysis of the relationship between government financial assistance and performance of small scale-hotels in Limpopo Province, South Africa - Silimela, Mashudu (My University, 2022)
This research aimed to find out if there is a link between government financial assistance to small-scale hotels and their financial performance in Limpopo province, South Africa. The objectives of the study is to examine the impact of government financial assistance on three financial performance measures, namely, sales turnover, net profits and net asset growth of the small scale-hotels. The research used a quantitative approach. Secondary panel data was collected from the financial statements of six small-scale hotels from 2015 to 2018. Data were analyzed using multiple regression model to arrive at the conclusion. The findings from the data analysis reveal that government financial assistance positively and significantly impact the growth in sales turnover and net profits of the small-scale hotels. Furthermore, the findings show that there is no significant relationship between government financial assistance and net asset growth of small scale hotels. The findings of this research have practical implications for the companies operating in the small-scale hotel sector. In addition, the findings of this study is important for the policy makers, as it highlights the policy gaps existing in the sector. The study recommends further research to examine the relationship between government financial assistance to small-scale hotels and their financial performance.
Thesis (MBA.) -- University of Limpopo, 2022
Keywords: Government financial assistance; Small-scale hotels; Financial performance; Sale turnover; Net profits; Total assets growth; Government spending policy; Finance, Public -- Accounting; Public investments; Corporate profits; Hotels -- Finance